Effectiveness of Agent Disinfectant Prior to Intravenous Catheter Placement on Infection and Potential Adverse Effects Among Neonates: A Systematic Review - Ina Islamia; Yeni Rustina; Mega Hasanul Huda; Robiyatul Adawiyah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Several disinfection agents have been proven to have controversial issues with neonates. These agents continue to be used to disinfect prior to the insertion of intravenous catheters, both peripheral and central venous catheters in neonatal care rooms. Objective to identify the effectiveness of disinfection agents used prior to intravenous catheter placement among neonates and the possible adverse events. A systematic review was conducted. Databases including Pubmed, Science Direct, Proquest, Ebscohost, Clinical Key Nursing, and Wiley were searched from inception to October 2024. The eligibility criteria were neonates who needed intravenous catheter placement (peripheral or central), with experimental research design, and articles written in English. The quality of studies was assessed depending on the study design. Our study is registered on PROSPERO number CRD42024618924. 1119 articles were found. After the screening processes, we finally included 7 articles. Disinfection agents frequently used in neonatal settings in the included studies were chlorhexidine (with varying concentrations), aqueous and alcohol-based, and povidone-iodine 10%. The disinfectant used prior to the insertion of the intravenous catheter was effective in reducing pathogen colonization on the skin and preventing bloodstream infection. Even so, there were some concerns regarding the adverse effects of the disinfectant agent used. The disinfection prior to invasive procedures in neonatal care is a debated topic. Despite this, inadequate disinfection poses more life-threatening due to the risk of bloodstream infection. Key factors to consider when choosing an appropriate topical agent disinfectant prior to intravenous catheter placement in neonates include gestational age, birth weight, and skin condition.